The reality of middle school teachers in Madinah using the Madrasati educational platform and a proposal for its development - Al-Harbi, Melook Humood; Al-Sharif, Basem Nayef (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of middle school teachers in Madinah’s use of the Madrasati educational platform, and to present a suggested vision for the development of its use in the educational process. A paragraph, divided into two axes: the reality of teachers’ uses of the Madrasati platform, and the teachers’ suggestions for its development. The results of the study revealed that the reality of the use of the Madrasati platform by middle school teachers in Madinah came with great appreciation, with an arithmetic average of (4.15) and a percentage (83%), as the responses came The study sample on the proposals to develop my school platform is very large, with an average of (4.41), and with a relative weight (88%). The study presented a proposed vision for the development of the Madrasati platform based on the reality of teachers’ use of the platform, and their responses to their proposals to develop it, in addition to the educational literature in this field. The need for the responsible authorities to adopt the proposed vision for developing the Madrasati platform, expanding the use of the platform and enhancing its use, and providing it with the necessary educational materials and resources for this.